Study on Wear and Morphological Behavior of Electron Beam Dose Irradiated Polyoxymethylene Copolymer (POM-C) - Rahman, Md. Shahinur; Lee, Heon-Ju; Yang, Jong-Keun; Lyakhov, Konstantin; Uddin, Muhammad Athar (Rajshahi University Journal of Science and Engineering, 2016)
Polyoxymethylene copolymer (POM-C) is the most prominent engineering thermoplastic consisting of repeating carbon-oxygen bonds in the form of oxymethylene groups (OCH2). It is widely used to make small gear wheels, ball bearings, precision parts, automotive and consumer electronics. In this study, the POM-C round blocks were irradiated with 165 KeV electron beam energy in five doses (100, 200, 300, 500 and 700 kGy) in vacuum condition at room temperature. The wear rate, surface hardness and morphological properties of electron beam dose irradiated POM-C blocks surfaces have been analyzed using pin on disk tribometer, optical microscopy, nano-indenter, Raman spectroscopy, 3D nano surface profiler and scanning electron microscopy (SEM). The electron beam irradiation transferred the wear phenomena of unirradiated POM-C sample from the abrasive wear (plough and cracks), adhesive wear (grooving/striation, micropitting) and scraping to mild scraping and striation for the 100 kGy dose irradiated POM-C sample due to cross-linking (macroscopic networks), chemical free radicals formations and partial physical modification (smoothness), which can be concluded from tribometer, optical microscopic, SEM and Raman spectroscopic observations. It also reduced the surface wear rate and average surface roughness with increasing microsurface hardness at threshold value of cross-linking among all unirradiated and others doses irradiated POM-C blocks. The level of tribological (wear and morphology) attribute improvement relies on the electron beam irradiation condition (energy and dose rate) depending on chemical and physical factors of polymeric materials.